Two Years Trend of Cervical Screening and Precancerous and Cancerous Lesion in Cervical Biopsy in Paropakar Maternity and Women’s Hospital - Vaidya, Karishma Malla; Baral, Gehanath; Shrestha, Bigya (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To determine the detection rate of cervical lesion by cervical Pap test and to see the ongoing trend of Pap testing in the hospital. Methods: The retrospective study was conducted in department of pathology, Paropakar Maternity and Women’s Hospital, Thapathali, Kathmandu, Nepal from 2016 to 2018. Pap testing sample received in the department were included in the study. All the data were retrieved from computers and registers at record section and histopathology unit. Results: There were 5.49% (1688 out of 30725) and 6.12% (1779 out of 29062) of gynecology out-patients had Pap test in first and second year respectively. Epithelial cells abnormalities were seen in 6.1% (104) and 4.83% (86) in first and second year respectively. Cervical biopsy sample in first year and second year had precancer and cancerous lesion in 29.55% (94 out of 318) and 22.01% (59 out of 268) in second year. Conclusions: Epithelial abnormalities seen in Pap test could detect quite a good proportion of abnormal cervical lesion in biopsy specimen of cervix.